Política, economia e democracia: as sabatinas no Senado Federal dos indicados ao Banco Central nos governos FHC e Lula - Albuquerque, Mateus Coelho Martins de (2019)
This essay is aimed at the sabatines held in the Comission of Economic Subjects of the brazilian Federal Senate, which had as objective the approval of those indicated by the Presidency of the Republic to the position of President of the Brazilian’s Central Bank. The chosen time cut adds the sabatines of Pérsio Arida (1995), Gustavo Loyola (1995), Gustavo Franco (1997), Francisco Lopes (1999), Armínio Fraga (1999) – in the two mandates of the presidency of Fernando Henrique Cardoso (1995-2002) – and Henrique Meirelles (2002), in the first mandete of the presidency of Lula da Silva (2003-2010). For the analytical method, was select the Content Analyses, wich extract relevant information form the corpus of the work, formed by the stenographic notes of the sessions. Theoretically, the work intends to proceed with a marxist analysis without abandoning the concept of ellites. Focuse in the actions of te senators during and with them formed a dialogical relationship with the presente confrontations in Brazillian economy, the problem that guides this research is: how the performance of the senators in the sabatines of the indicateds to the Central Bank during the governmantes of FHC and Lula reflect the macroeconomical conflict of the time cut?